SISTEM INFORMASI PENJUALAN DAN PERSEDIAAN PRODUK PERALATAN PERTANIAN BERBASIS WEB - Duma Yanti Siringoringo; Volvo Sihombing; Masrizal Masrizal (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
The rapid development of technology has brought humans into a life side by side with information and technology itself. Nowadays, more and more companies need fast and accurate information services. Processing of sales and inventory data at the Growmart (Farmer Business Branch) Bagan Batu company which still uses the manual method makes recording sales data and printing reports slow and less efficient. To solve this problem, a web-based sales and inventory information system for agricultural equipment products was designed. This web-based information system was built using the PHP programming language and the Cascading Style Sheet (CSS) as content representation, and database processing using MySQL. The result of this research is an information system that helps the sales admin section of the Growmart company to input sales data and equipment product inventory easily, quickly and efficiently.